Correcting image blur in spiral, retraced in/out (RIO) acquisitions using a maximized energy objective. Issue 3 (13th November 2018) - Allen, Steven P.; Feng, Xue; Fielden, Samuel W.; Meyer, Craig H.
Abstract : Purpose: Images acquired with spiral k‐space trajectories can suffer from off‐resonance image blur. Previous work showed that averaging 2 images acquired with a retraced, in/out (RIO) trajectory self‐corrects image blur so long as off‐resonant spins accrue less than 1 half‐cycle of relative phase over the readout. Practical scenarios frequently exceed this threshold. Here, we derive and characterize a more‐robust off‐resonance image blur correction method for RIO acquisitions. Methods: Phantom and human volunteer data were acquired using a RIO trajectory with readout durations ranging from 4 to 60 ms. The resulting images were deblurred using 3 candidate methods: conventional linear correction of the component images; semiautomatic deblurring of the component images using an established minimized phase objective function; and semiautomatic deblurring of the average of the component images using a maximized energy objective function, derived below. Deblurring errors were estimated relative to images acquired with 4 ms readouts. Results: All 3 methods converged to similar solutions in cases where less than 2 and 4 cycles of phase accrued over the readout in in vivo and phantom images, respectively (<13 ms readout at 3T). Above this threshold, the linear and minimized phase methods introduced several errors. The maximized energy function provided accurate deblurring so long as less than 6 and 10 cycles of phase accrued over the readout in in vivo and phantom images, respectively (<34 ms readout at 3T). Conclusion: The maximized energy objective function can accurately deblur RIO acquisitions over a wide spectrum of off resonance frequencies.